The impact of a self-management program on exercise adherence among patients discharged after coronary artery bypass grafts: A quasi-experimental study in Thailand - Sudarat Tippinit; Rapin Polsook (Belitung Raya Foundation, Indonesia, 2023)
Background: Exercise adherence is essential for maintaining the physical and mental health of patients after coronary artery bypass grafts (CABG). However, adherence is often poor, particularly in the early weeks after hospital discharge, leading to adverse health outcomes. Therefore, implementing self-management programs is crucial to promote and sustain long-term exercise adherence among these patients. Objective: This study aimed to examine the impact of self-management programs on exercise adherence in post-CABG patients. Methods: A quasi-experimental posttest-only control group study was conducted from April to November 2022 at Surat Thani Hospital in Thailand. Forty post-CABG patients were gender and age-matched and randomly assigned to either the control group (n = 20) or the experimental group (n = 20). The experimental group participated in a six-week self-management program for exercise adherence, utilizing telephone and LINE applications, while the control group received standard care. Data were collected using validated exercise adherence rating scales and a self-management questionnaire. Descriptive statistics and independent t-tests were employed for data analysis. Results: The mean exercise adherence score in the control group was 9.30 (SD = 4.91), whereas it was 21.30 (SD = 3.20) in the experimental group. The experimental group, which received the self-management program, exhibited significantly higher exercise adherence scores compared to the control group (t = 9.16, df = 32.65, p <0.001). Conclusions: This study demonstrates the effectiveness of a post-CABG self-management program in improving exercise adherence. Nurses play a crucial role in promoting and enhancing self-management during the pre-and post-discharge phases, and regular phone or LINE application contacts can have a positive impact on post-CABG patients. Policymakers should consider implementing self-management programs to encourage patients to maintain their exercise routines, leading to improved physical and mental well-being.